Fundamentals of investment management - Hirt, Geoffrey A.; Block, Stanley B. (Irwin/McGraw-Hill series in finance, insurance and real estate, 2012)
Presenting applied theory alongside real-world examples, this title provides a survey of the important areas of investments: valuation, the marketplace, fixed income instruments and markets, equity instruments and markets, derivative instruments, and a cross-section of topics, such as international markets and mutual funds